Gricean Maxim Analysis of Beatrice's Utterances in `Divergent` Movie - Sri Winda Utami; Yunita Nugraheni; Diana Hardiyanti (Universitas Muhammadiyah Semarang, 2017)
The main problem of research focuses on how are the implementation of Paul Grice cooperative principle of Beatrices utterances in Divergent movie. Cooperative principle is aimed to get the effective communication as required. Violating of cooperative principle, it means that the communication result is not effective. The research is purposed to identify the implementation of Paul Grice cooperative principle of Beatrices utterances in Divergent movie. The method of research is observing Divergent movie and transcribing the data by purposive sampling. The collected data are analyzed by theoretical of cooperative principle and context of situation approach. The result of research shows that the cooperative principle is not always obeyed by Beatrice. Based on 38 data of Beatrices utterances, submissive of cooperative principle consists of 61 % data, while violation of cooperative principle consists of 39% data. The percentages are; submissive of cooperative principle content with 37% quantity maxim, 5% quality maxim, 11% relation maxim, 8% manner maxim. Violation of cooperative principle, they are: 18% quantity maxim, 8% quality maxim, 5% relation maxim, 8% manner maxim. It can be concluded that submissive of cooperative principle are mostly obeyed by Beatrice.